HUBUNGAN ANTARA PENGGUNAAN MEDIA FACEBOOK DAN KREATIVITAS BELAJAR DENGAN KEMAMPUAN MEMBUAT BLOG - Wike Retna Wellyanti; Yus'aini Na (Akademika : Jurnal Teknologi Pendidikan, 2018)
Research in the world of education is expected to contribute ideas in the development of knowledge, especially the development of quality education process in influencing students in meeting the ability to create blogs in State Junior High School Lemahwungkuk District, Cirebon City. Practically, this research is expected to provide valuable inputs for schools that are the location of research, and other schools that havesimilarities related to the relationship between the use of facebook media and the creativity of student learning with the ability to create a blog. This research is a descriptive analytic survey research at SMP Negeri 3, SMP Negeri 13 and SMP Negeri 15 Kecamatan Lemahwungkuk Kota Cirebon with affordable population of 749 students and analyzed by using correlation analysis and linear regression, both simple linear andlinear double. The results show, firstly, there is no significant positive relationship between the use of facebook media on the ability to create a blog. Second, explaining about the positive relationship that is not significant between students' learning creativity to the ability to create a blog. Third, it was found that there was no significant positive relationship between the use of facebook media (X1) and students' learning creativity simultaneously on the ability to create blog (Y).Based on the above results, this study provides advice to the Education Department of Cirebon City for socialization to the entire community, especially students in the City of Cirebon about how the use of social media is good.